Influence of Graphene Oxide on Interfacial Transition Zone of Mortar. (19th February 2020) - Sun, Hongfang; Ren, Zhili; Ling, Li; Memon, Shazim Ali; Ren, Jie; Liu, Bing; Xing, Feng
Abstract : In this paper, the influence of graphene oxide (GO) on the microstructure of interfacial transition zone (ITZ) in cement mortar was investigated through image analysis (IA) of backscattered electron (BSE) micrographs. The results showed that the incorporation of GO significantly reduced the thickness of ITZ. The porosity in ITZ and bulk paste decreased due to the introduction of GO; meanwhile, the compressive strength of the mortar samples was improved. The addition of GO also narrowed the gap between the porosity of ITZ and bulk paste, and therefore, the entire microstructure of mortar became more homogenous. Based on the above results, the model to predict the compressive strength of mortar was modified for better precision. The improved prediction model indicated that the difference between the compressive strength of ITZ and bulk paste was reduced upon the refinement of ITZ by GO.